Nature and Trends of Crime against Dalits - Akshat, Pushpam; Singh, Rajeev Kumar (Economic and Political Weekly, 2024)
Social stratification in India is based on caste, which is one of the important sources of ascribed identity.
Keywords: Crime Against Dalits; Dalit Movements; Scheduled Castes; Untouchables; Population